A novel micromotion measurement method to gain instructive insight into the acetabular bone-implant interface. (December 2020) - Heilemann, Martin; Wendler, Toni; Münst, Philipp; Schleifenbaum, Stefan; Scholz, Roger; Voigt, Christian
Highlights: Pin-sleeve sensors transmit bone-implant micromotion from their interface out. Optical tracking of sensors by 3D image correlation. Calculation of bone-implant micromotion in six degrees of freedom. Micromotion measurement over the entire acetabular bone-implant interface. Recognition of weak spots of acetabular bone-implant compound. Abstract: In total hip arthroplasty insufficient primary stability with excessive bone-implant micromotion is a major reason for aseptic loosening at the acetabular cup implant. In the literature, several methods were proposed for in vitro micromotion measurement, but none is capable of six degrees of freedom measurement at a large number of measuring points over the entire acetabular bone-implant interface, which was the aim of the current scientific work. A pin-sleeve sensor system was developed and an appropriate installing technique was incorporated. Micromotions were transmitted from the internal interface to the accessible periphery. Motion data of the sensors were optically tracked. A calculation algorithm was conceived, discretizing superimposed rotational and translational components. The method was tested and subsequently applied to a cementless revision cup implanted into an artificial hemipelvic bone featuring a typical bone defect. Using eighteen sensors in positions across the acetabular bone-implant interface, micromotion magnitudes from 59 µm ± 2 µm to 222 µm ± 5 µm were detected. Allocation of micromotion complied with case specific anticipations. The novel pin-sleeve sensors transmitted interface micromotion to the accessible periphery as desired. The measurement method enables instructive insights into three-dimensional bone-implant micromotion and may prospectively be used to evaluate different implant systems.